La actividad en España del obispo de Michoacán y de Tlaxcala Antonio Ruiz de Morales - Paniagua Pérez, Jesús (Estudios humanísticos. Geografía, historia y arte, 1994)
This article is intended to offer a preview of the work and character of Antonio Ruiz de Morales. This sixteenth century figure, a noted humanist who attained great fame in his day, was a cleric in the Order of Santiago (Saint James). Thanks to his merits, he was appointed Bishop, first of Michoacán and latert of the Diocesis of Puebla-Tlaxcala. We are currently engaged in preparing an edition of his works, which show the intellectual worth of this prelate, who had very close connexions with the leading lights of the intelligentsia of his times, such as Benito Arias Montano, Jerónimo Gudiel, Ambrosio de Morales, and others.